2017
DOI: 10.5539/jas.v9n7p68
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Puerariae Radix on the Breast Tumor Incidence in Rats Treated with DMBA

Abstract: Puerariae Radix (PR) is the root of Pueraria lobata, an herb widely used in traditional Chinese medicine and as a food seasoning. Owing to its potential anti-oxidative ability, the effects of PR on the inhibition of breast tumors were investigated in this study using the 7,12-dimethylbenz[a]anthracene (DMBA)-treated rat model. Thirty-two female Sprague-Dawley rats were randomly assigned to one of four different treatment groups, with or without PR and/or DMBA administration. At the age of 177 days, all rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(45 reference statements)
2
2
0
Order By: Relevance
“…We found that total leukocytes of breast cancer models noticeably increased after 20 weeks, while the number of total leukocytes of normal group were steady during experiment (Table 1). These results were consistent with Chen report [11]. The authors suggested that treatment with DMBA 75 mg/ kg body weight resulted in decrease of body weight and the number of erythrocytes, but elevation of total leukocytes and lymphocytes.…”
Section: Changes Of Body Weight the Number Of Peripheral Erythrocytes And Leukocytessupporting
confidence: 92%
“…We found that total leukocytes of breast cancer models noticeably increased after 20 weeks, while the number of total leukocytes of normal group were steady during experiment (Table 1). These results were consistent with Chen report [11]. The authors suggested that treatment with DMBA 75 mg/ kg body weight resulted in decrease of body weight and the number of erythrocytes, but elevation of total leukocytes and lymphocytes.…”
Section: Changes Of Body Weight the Number Of Peripheral Erythrocytes And Leukocytessupporting
confidence: 92%
“…Lymphocytes fights cancer, with low levels of it in the blood encourages a relapse and decreased survival rates, while higher lymphocyte count increases the overall survival [16]. These results are in commensurate with those of Chen, et al [20], which showed that Pueriariae radix was able to reduce WBC, Neutrophil and lymphocyte levels of DMBA-induced mammary cancer. Table 4 shows the Blood platelets concentration of DMBA treated albino rats, given aqueous extract of the various plants.…”
Section: Discussionsupporting
confidence: 58%
“…Studies in the field of modern chemistry and medicine have shown that the main chemical constituents of Pueraria lobata include isoflavones, triterpenes, coumarins, and alkaloids [ 8 ]. It was reported that the extract of Puerariae Radix and its monomeric compounds have the effects on antioxidation [ 9 ], antihigh blood pressure [ 10 ], anticancer [ 11 ], antidiabetes/nephropathy [ 12 ], and neuroprotective [ 13 ].…”
Section: Introductionmentioning
confidence: 99%